“Spiritual Delicacies or Games Useful to Men Banished from the Earthly Paradise to the Heavenly Paradise” by Alberyk Kościński. Concerning the Spiritual Thought of the 17th Century - Kaczor-Scheitler, Katarzyna (Respectus Philologicus, 2015)
The article is one of the first attempts to present the works of Alberyk Kościński whose Spiritual Delicacies or Games Useful to Men Banished from the Earthly Paradise to the Heavenly Paradise (Poznań 1695) was aimed at helping nuns or potential recipients to perfect their inner self. The article discusses the three goals of meditation mentioned by Kościński (“elimination of imperfections, the acquisition of holy virtues and unison with God”) which relate to the three stages of spiritual life (purging, enlightenment, and unison). Thus, the article adds to the picture of the views presented by other authors.However, the innovation lies in the motif of “game” as an inner activity stimulating the spiritual sphere and encouraging spiritual transformation, as described in Kościński’s work. The article focuses on the role of the metaphorical images used by the clergyman to describe the meditative act: the internal transformation, the experience of closeness to and unity with God. Thus, the article emphasizes the need for meditative practice discussed by Kościński, i.e., the titular “spiritual delicacies” which can help one achieve eternal life.